1987
DOI: 10.1177/0013164487471035
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Attitudes toward Computer Usage Scale

Abstract: An Attitudes-Toward-Computer Usage Scale (ATCUS) was developed in two studies. In the first study, 40 items were administered to 365 undergraduate students to assess attitudes toward the use of computers and computer-related mechanisms. The scale was found to have high internal consistency and was significantly correlated with two other scales measuring attitudes toward computers. Sex differences were also found. Based on factor analysis results, the scale was reduced to 20 items and administered to 351 underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 6 publications
1
37
1
Order By: Relevance
“…Overall, computer user attitude scores were high for all respondents. This is consistent with recent studies and different from what was reported in earlier studies [34], suggesting an upward change in user's attitude toward computers over the years. Table 3 provides pre-and post-training scores for computer self-efficacy and Internet self-efficacy for all respondents.…”
Section: Data Analysis and Resultssupporting
confidence: 87%
“…Overall, computer user attitude scores were high for all respondents. This is consistent with recent studies and different from what was reported in earlier studies [34], suggesting an upward change in user's attitude toward computers over the years. Table 3 provides pre-and post-training scores for computer self-efficacy and Internet self-efficacy for all respondents.…”
Section: Data Analysis and Resultssupporting
confidence: 87%
“…Previously, the opposite might have been the case. Popovich, Hyde, Zakrajsek, and Blumer (1987) found that women's attitudes toward computers were significantly more negative than men's on most aspects of computer usage. Terlecki and Newcombe (2005), on the other hand, report more recent Web statistics showing that women marginally surpass men in their Internet usage; but they also found that women lag behind men in using computers in spatial activities.…”
Section: Discussionmentioning
confidence: 92%
“…The first questionnaire was aimed at assessing the dimensions of attitude toward art (4 items; Stokmans 1999) and attitude toward technology (6 items;Popovich et al 1987). The second questionnaire was aimed at assessing their experience in using the multimedia guide along diverse dimensions (all as Likert scales).…”
Section: Assessing the Adaptive Multimedia Guide Based On Like-o-metermentioning
confidence: 99%